Antibacterial fiber hydrogel with high mechanical strength as well as preparation method and application thereof

By loading polyhexamethylene biguanide, o-vanillin and gadolinium ions in the fiber hydrogel, combined with silk fibroin and electrospinning technology, fiber hydrogels with high mechanical strength and excellent antibacterial effects were prepared, which solved the problems of low mechanical strength of existing hydrogels and difficulty in controlling antibacterial release, and significantly improved the wound healing effect.

CN119499438APending Publication Date: 2025-02-25SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411739558.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing hydrogels have low mechanical strength and cannot effectively control the release of antibacterial agents, which limits their application in the treatment of trauma infection.

Method used

A fiber hydrogel loaded with polyhexamethylene biguanide, orthovanillin and gadolinium ions was developed, and an antibacterial hydrogel with a directional fiber structure was prepared by using silk fibroin as a matrix component, combined with electrospinning technology.

Benefits of technology

A high mechanical strength antibacterial hydrogel can effectively inhibit bacterial growth and biofilm formation, significantly improve wound healing effect, and demonstrate good biocompatibility and cell proliferation promotion ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499438A_ABST
    Figure CN119499438A_ABST
Patent Text Reader

Abstract

The invention discloses antibacterial fiber hydrogel with high mechanical strength as well as a preparation method and application thereof, and belongs to the technical field of biomedicine. The invention develops the antibacterial fiber hydrogel with high mechanical strength, and the antibacterial fiber hydrogel can closely simulate a natural ECM environment. The preparation method comprises the following steps: reacting polyhexamethylene biguanide with vanillin to form a Schiff base ligand PV, and then coordinating with gadolinium ions to form a PVG compound; silk fibroin is used as a matrix, a PVG compound is introduced into the fiber hydrogel through electrostatic spinning, a topological structure with anisotropy is formed, and the finally obtained antibacterial fiber hydrogel shows strong antibacterial activity and can effectively inhibit bacterial growth and biofilm formation. In addition, the fiber directivity and high mechanical strength of the antibacterial fiber hydrogel promote the cell function, and cell attachment and proliferation are facilitated. Therefore, the antibacterial fiber hydrogel prepared by the invention has huge potential in wound infection treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedicine, and in particular to an antibacterial fiber hydrogel with high mechanical strength and a preparation method and application thereof. Background Art

[0002] As the primary barrier against external pathogens, the skin is particularly vulnerable to invasion by resident and transient bacteria, especially when its structural integrity is compromised. 5 A threshold of 1 bacterium is sufficient to cause tissue damage by releasing inflammatory cytokines. Currently, antibiotics are the most common antimicrobial agents, but they are prone to drug resistance and may exhibit various toxic side effects. To address these problems, researchers have explored alternative antimicrobial agents, including metal ions, antimicrobial peptides, and plant extracts. However, these antimicrobial agents often have some disadvantages, such as cytotoxicity, high production costs, and difficulty in obtaining, which limit their clinical application. Although extensive progress has been made in the research of antimicrobial dressings, the options available on the market are still limited, mainly relying on silver ions (Ag + ) release to provide antimicrobial properties. + It is widely recognized for its powerful bactericidal effect, but it may also cause systemic and local toxic side effects.

[0003] The beneficial role of local moist environment in wound healing highlights the potential of hydrogel dressings. Although the advantages of hydrogel dressings have been well studied, most studies have focused on volumetric hydrogels, which typically have a honeycomb-like lattice structure that deviates from the structure of the extracellular matrix (ECM). These volumetric hydrogels generally exhibit low mechanical strength and have difficulty in controlling the release of antimicrobial agents. Given these challenges, the development of new antimicrobial dressings is imperative. Summary of the invention

[0004] In order to solve the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide an antibacterial fiber hydrogel with high mechanical strength and a preparation method and application thereof, so as to solve the problem that the existing hydrogel has low mechanical strength and cannot control the release of antibacterial agents.

[0005] The technical solution of the present invention to solve the above technical problems is as follows: The present invention provides an antibacterial fiber hydrogel with high mechanical strength, including a fiber hydrogel loaded with polyhexamethylene biguanide, o-vanillin and gadolinium ions; wherein the fiber hydrogel also includes silk fibroin.

[0006] 1. An antibacterial fiber hydrogel with high mechanical strength, characterized in that it includes a fiber hydrogel loaded with polyhexamethylene biguanide, o-vanillin and gadolinium ions; wherein the fiber hydrogel also includes silk fibroin.

[0007] The present invention provides a method for preparing an antibacterial fiber hydrogel with high mechanical strength, comprising the following steps: (1) After removing the gelatin from the silkworm cocoons and washing them, the products are dried and dissolved in a solvent, reacted at 75-85°C for 1-2 hours, dialyzed and centrifuged, purified and freeze-dried to obtain silk fibroin; (2) dissolving polyhexamethylene biguanide and o-vanillin in a solvent respectively, then dropping o-vanillin into the polyhexamethylene biguanide solution, reacting for 2.5-3.5 hours, and removing the solvent to obtain a PV composite; (3) Dissolving the PV complex in a solvent, then adding a solution containing gadolinium ions to react for 2-3 hours, and then removing the solvent to obtain the PVG complex; (4) The silk fibroin prepared in step (1) is dissolved in a solvent, and then the PVG complex prepared in step (3) is added to prepare a fiber hydrogel. The product is vacuum dried, cross-linked, and then hydrated to obtain a hydrogel.

[0008] Furthermore, in step (1), the solvent is a mixed solution of CaCl2 / ethanol / H2O, and the molar ratio of CaCl2 / ethanol / H2O is 1:1-5:5-10.

[0009] Furthermore, in step (2), the concentration of polyhexamethylene biguanide is 0.025-0.125 g / mL; the concentration of o-vanillin is 1.25-2.5 mg / mL; and the solvent is methanol.

[0010] Furthermore, the solution containing gadolinium ions in step (3) is at least one of gadolinium chloride, gadolinium nitrate, gadolinium oxalate, gadolinium acetate and gadolinium sulfate; the concentration of the PV complex is 0.0625-0.025 g / mL; and the solvent is methanol.

[0011] Furthermore, in step (4), the mass ratio of silk fibroin to PVG complex is 20-40:1; and the solvent is hexafluoroisopropanol and formic acid.

[0012] Furthermore, the preparation parameters of the fiber hydrogel in step (4) are: voltage 15-25 kV, distance between the needle and the collector 10-20 cm, flow rate 2-3 mL / h, and rotation speed 800-2400 rpm.

[0013] The present invention also provides an application of an antibacterial fiber hydrogel with high mechanical strength in preparing a wound infection medicine.

[0014] Furthermore, traumatic infections include burn wounds, diabetic foot ulcers, pressure injuries and venous ulcers of the lower limbs.

[0015] Furthermore, the medicine is a wound dressing.

[0016] The present invention has the following beneficial effects: (1) The present invention prepares a novel antibacterial hydrogel, which is characterized by an oriented fiber structure and is used to treat wound infection. Silk fibroin (SF) is selected as the matrix component because of its excellent biocompatibility, mechanical strength and ability to support cell adhesion and proliferation. Polyhexamethylene biguanide (PHMB) and gadolinium ion (Gd 3+ ) are added as antimicrobial ingredients because of their high biocompatibility and low risk of bacterial resistance development. PHMB interacts with negatively charged bacterial cell membranes, resulting in increased membrane permeability, which triggers bacterial death. PHMB is able to selectively bind to prokaryotic chromosomes, further enhancing its antimicrobial potency while maintaining low cytotoxicity. 3+ By inhibiting enzyme activity or interfering with the calcium binding site on the receptor protein, the bacterial signaling pathway is destroyed, thereby causing bacterial death, which is different from traditional antibacterial metal ions such as silver ions (Ag + ) and copper ions (Cu 2+ ) is different, Gd 3+ The cytotoxicity of the drug was significantly lower, which enhances its potential for clinical application.

[0017] (2) In order to ensure the stable binding of the antibacterial components in the hydrogel and maintain its lasting antibacterial effect on wounds, o-vanillin (VAN) was used as an additive. VAN can react with PHMB through Schiff bases to bind two VAN molecules at both ends of the PHMB molecule. These two Schiff bases can react with Ga 3+ Form a coordination bond. Because PHMB and Ga 3+ Both are positively charged. Without VAN, they will repel each other and cannot form PVG. VAN can also enhance the hydrogen bonding and ionic interaction between PVG and silk fibroin, thus helping to form a stable bond. In addition, the experimental results of this application show that PHMB, Ga 3+ The combination with o-vanillin also played a synergistic role, enhancing the mechanical properties and antibacterial effects of the antibacterial fiber hydrogel.

[0018] (3) VAN, as a naturally derived fragrance, is widely used in the medical field and has the additional advantage of masking the unpleasant odor produced by bacterial metabolites in infected wounds, thereby improving the quality of life of patients.

[0019] (4) Using silk fibroin (SF) and PVG as raw materials, we prepared fiber hydrogels with oriented structures (SF-PVGA) by electrospinning technology, and then processed them by ethanol cross-linking and rehydration. SF-PVGA hydrogels showed strong antibacterial properties and combined the intrinsic advantages of bulk hydrogels, such as excellent hydrophilicity and flexibility, with the advantages of electrospun fibers, such as large specific surface area, good mechanical properties and cell function regulation, showing its application prospects in the treatment of wound infections. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Figure 1 is the characterization of PVG; Figure A is the synthesis process of PVG; Figure B is the UV-visible absorption spectra of VAN, PHMB, PV and PVG; Figure C is the FT-IR spectrum; Figure 2 Characterization of fiber hydrogel; Figure A is the FT-IR spectrum; Figure B is the image of SF fiber hydrogel treated with anhydrous ethanol before and after cross-linking; Figure C is the SEM image, Figure D is the fiber diameter distribution diagram; Figure E is the average fiber diameter; Figure F is Young's modulus (n=3); Figure G is the stress-strain curve of SF, SF-P, SF-PV and SF-PVG fiber hydrogel; Figure 3 Figure 1 shows the adhesion of bacteria on different fiber hydrogels; Figure A is a SEM image of bacteria adhering to fiber hydrogels; Figure B is a photo of bacteria adhering to different hydrogels; Figure 4 Figure 1 shows the biofilm formation on different fiber hydrogels; Figure A shows the SEM images of biofilm formation on different fiber hydrogels; Figure B shows photos of bacteria attached to different hydrogels; Figure 5 The hemolytic properties of different fiber hydrogels; Figure 6 The biocompatibility of SF-PVG fiber hydrogel; Figure 7 The proliferation of human umbilical vein endothelial cells (HUVECs) cultured on different fiber hydrogels at 1, 3, and 5 days; Figure 8 The attachment and expansion of HUVECs cells on different fiber hydrogels; Fig. 9 DAPI and Phalloidin staining images of HUVECs cells cultured on different fiber hydrogels for 3 days; Fig.10The effects of different fiber hydrogels in treating wounds infected with Staphylococcus aureus in rats; Figure A is a photo of mouse wounds after 7 days of treatment with different fiber hydrogels; Figure B is a quantitative analysis of the wound area of ​​mice after treatment with different fiber hydrogels; Figure C is a photo of an agar plate of homogenized wound tissue of mice cultured from different fiber hydrogels; Figure D is the bacterial survival rate corresponding to different fiber hydrogels. DETAILED DESCRIPTION

[0021] The following examples are only used to explain the present invention and are not intended to limit the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0022] Example 1 An antibacterial fiber hydrogel (SF-PVG) with high mechanical strength includes a fiber hydrogel loaded with polyhexamethylene biguanide, o-vanillin and gadolinium ions; wherein the fiber hydrogel also includes silk fibroin. The preparation method thereof includes the following steps: (1) Extraction of silk fibroin (SF): 5 g of silk cocoons were placed in 1000 mL of 0.02 M sodium carbonate (Na2CO3) solution and degummed at 100 °C for 1 h. Rinse with deionized water (DI water) three times to remove sericin, and then dry in an oven at 60 °C for 12 h. The degummed silk fibroin (SF) was dissolved in a ternary solvent system of CaCl2 / ethanol / H2O at 75 °C for 1 h. The obtained SF solution was dialyzed with a dialysis bag with a molecular weight cutoff of 3500, and the dialysate was DI water. The dialysis was performed for 3 days, during which the water was changed 3 times a day. Impurities and precipitated proteins were removed by high-speed centrifugation at 9000 rpm at 4 °C for 20 min, and the purified SF was then freeze-dried; (2) Synthesis of PHMB-VAN-Gd (PVG): Dissolve 1g PHMB in 40mL methanol and stir until completely dissolved. The reaction temperature is 70℃. Dissolve 50mg VAN in 1mL methanol and add it dropwise to the PHMB solution. The liquid quickly turns yellow. After stirring for 3h, remove the solvent using a rotary evaporator to obtain dry PV. Then, dissolve 0.5g PV in 40mL methanol, add 0.4g Gd(NO3)3·6H3O, react at 70℃ for 2h, remove the solvent, and obtain PHMB-VAN-Gd complex (PVG). (3) Preparation of SF-PVG hydrogel: 1 g SF was dissolved in a mixed solution of 7% (w / w) hexafluoroisopropanol (HFIP) and 98% (w / w) formic acid (volume ratio 9:1). 75 mg PVG was added to the SF solution to prepare SF-PVG fiber hydrogel. The hydrogel was prepared using an electrospinning device (TongLi, China) under the following parameters: voltage 20 kV, distance between needle and collector 15 cm, flow rate 2 mL / h, rotation speed 800 rpm, and the collected fiber hydrogel was vacuum dried at 60 °C for 12 h, then cross-linked in anhydrous ethanol and rehydrated in phosphate buffered saline (PBS).

[0023] Example 2 An antibacterial fiber hydrogel (SF-PVGA) with high mechanical strength includes a fiber hydrogel loaded with polyhexamethylene biguanide, o-vanillin and gadolinium ions; wherein the fiber hydrogel also includes silk fibroin. The preparation method thereof is the same as that of Example 1 except that the rotation speed of the electrospinning device is 2400 rpm, and other steps and parameters are the same as those of Example 1.

[0024] Comparative Example 1 A fiber hydrogel (SF) includes silk fibroin. The preparation method thereof includes the following steps: (1) Extraction of silk fibroin (SF): 5 g of silk cocoons were placed in 1000 mL of 0.02 M sodium carbonate (Na2CO3) solution and degummed at 100 °C for 1 h. Rinse with deionized water (DI water) three times to remove sericin, and then dry in an oven at 60 °C for 12 h. The degummed silk fibroin (SF) was dissolved in a ternary solvent system of CaCl2 / ethanol / H2O at 75 °C for 1 h. The obtained SF solution was dialyzed with a dialysis bag with a molecular weight cutoff of 3500, and the dialysate was DI water. The dialysis was performed for 3 days, during which the water was changed 3 times a day. Impurities and precipitated proteins were removed by high-speed centrifugation at 9000 rpm at 4 °C for 20 min, and the purified SF was then freeze-dried; (2) Preparation of SF hydrogel: 1 g SF was dissolved in a mixed solution of 7% (w / w) hexafluoroisopropanol (HFIP) and 98% (w / w) formic acid (volume ratio 9:1). The hydrogel was prepared using an electrospinning device (TongLi, China) under the following parameters: voltage 20 kV, distance between needle and collector 15 cm, flow rate 2 mL / h, rotation speed 800 rpm. The collected fiber hydrogel was vacuum dried at 60 °C for 12 h and then cross-linked in anhydrous ethanol and rehydrated in phosphate buffered saline (PBS).

[0025] Comparative Example 2 A fiber hydrogel (SF-Gd) includes a fiber hydrogel loaded with gadolinium ions; wherein the fiber hydrogel also includes silk fibroin. The preparation method thereof includes the following steps: (1) Extraction of silk fibroin (SF): 5 g of silk cocoons were placed in 1000 mL of 0.02 M sodium carbonate (Na2CO3) solution and degummed at 100 °C for 1 h. Rinse with deionized water (DI water) three times to remove sericin, and then dry in an oven at 60 °C for 12 h. The degummed silk fibroin (SF) was dissolved in a ternary solvent system of CaCl2 / ethanol / H2O at 75 °C for 1 h. The obtained SF solution was dialyzed with a dialysis bag with a molecular weight cutoff of 3500, and the dialysate was DI water. The dialysis was performed for 3 days, during which the water was changed 3 times a day. Impurities and precipitated proteins were removed by high-speed centrifugation at 9000 rpm at 4 °C for 20 min, and the purified SF was then freeze-dried; (2) Preparation of SF-Gd hydrogel: 1 g SF was dissolved in a mixed solution of 7% (w / w) hexafluoroisopropanol (HFIP) and 98% (w / w) formic acid (volume ratio 9:1), and 0.4 g Gd(NO3)3·6H3O was added to the SF solution to prepare SF-Gd fiber hydrogel. The hydrogel was prepared using an electrospinning device (TongLi, China) under the following parameters: voltage 20 kV, distance between needle and collector 15 cm, flow rate 2 mL / h, rotation speed 800 rpm, and the collected fiber hydrogel was vacuum dried at 60 °C for 12 h, then cross-linked in anhydrous ethanol and rehydrated in phosphate buffered saline (PBS).

[0026] Comparative Example 3 An antibacterial fiber hydrogel (SF-P) includes a fiber hydrogel loaded with polyhexamethylene biguanide; wherein the fiber hydrogel also includes silk fibroin. The preparation method thereof includes the following steps: (1) Extraction of silk fibroin (SF): 5 g of silk cocoons were placed in 1000 mL of 0.02 M sodium carbonate (Na2CO3) solution and degummed at 100 °C for 1 h. Rinse with deionized water (DI water) three times to remove sericin, and then dry in an oven at 60 °C for 12 h. The degummed silk fibroin (SF) was dissolved in a ternary solvent system of CaCl2 / ethanol / H2O at 75 °C for 1 h. The obtained SF solution was dialyzed with a dialysis bag with a molecular weight cutoff of 3500, and the dialysate was DI water. The dialysis was performed for 3 days, during which the water was changed 3 times a day. Impurities and precipitated proteins were removed by high-speed centrifugation at 9000 rpm at 4 °C for 20 min, and the purified SF was then freeze-dried; (2) Preparation of SF-P hydrogel: 1 g SF was dissolved in a mixed solution of 7% (w / w) hexafluoroisopropanol (HFIP) and 98% (w / w) formic acid (volume ratio 9:1). 1 g PHMB was added to the SF solution to prepare SF-P fiber hydrogel. The hydrogel was prepared using an electrospinning device (TongLi, China) under the following parameters: voltage 20 kV, distance between needle and collector 15 cm, flow rate 2 mL / h, rotation speed 800 rpm, and the collected fiber hydrogel was vacuum dried at 60 °C for 12 h, then cross-linked in anhydrous ethanol and rehydrated in phosphate buffered saline (PBS).

[0027] Comparative Example 4 An antibacterial fiber hydrogel (SF-PV) includes a fiber hydrogel loaded with polyhexamethylene biguanide and o-vanillin; wherein the fiber hydrogel also includes silk fibroin. The preparation method thereof includes the following steps: (1) Extraction of silk fibroin (SF): 5 g of silk cocoons were placed in 1000 mL of 0.02 M sodium carbonate (Na2CO3) solution and degummed at 100 °C for 1 h. Rinse with deionized water (DI water) three times to remove sericin, and then dry in an oven at 60 °C for 12 h. The degummed silk fibroin (SF) was dissolved in a ternary solvent system of CaCl2 / ethanol / H2O at 75 °C for 1 h. The obtained SF solution was dialyzed with a dialysis bag with a molecular weight cutoff of 3500, and the dialysate was DI water. The dialysis was performed for 3 days, during which the water was changed 3 times a day. Impurities and precipitated proteins were removed by high-speed centrifugation at 9000 rpm at 4 °C for 20 min, and the purified SF was then freeze-dried; (2) Synthesis of PHMB-VAN (PV): Dissolve 1 g of PHMB in 40 mL of methanol and stir until completely dissolved. The reaction temperature is 70 °C. Dissolve 50 mg of VAN in 1 mL of methanol and add it dropwise to the PHMB solution. The liquid quickly turns yellow. After stirring for 3 h, use a rotary evaporator to remove the solvent to obtain dry PV. (3) Preparation of SF-PV hydrogel: 1 g SF was dissolved in a mixed solution of 7% (w / w) hexafluoroisopropanol (HFIP) and 98% (w / w) formic acid (volume ratio 9:1). 75 mg PV was added to the SF solution to prepare SF-PV fiber hydrogel. The hydrogel was prepared using an electrospinning device (TongLi, China) under the following parameters: voltage 20 kV, distance between needle and collector 15 cm, flow rate 2 mL / h, rotation speed 800 rpm, and the collected fiber hydrogel was vacuum dried at 60 °C for 12 h, then cross-linked in anhydrous ethanol and rehydrated in phosphate buffered saline (PBS).

[0028] Comparative Example 5 An antibacterial fiber hydrogel (SF-P-Gd) includes a fiber hydrogel loaded with polyhexamethylene biguanide and gadolinium ions; wherein the fiber hydrogel also includes silk fibroin. The preparation method thereof includes the following steps: (1) Extraction of silk fibroin (SF): 5 g of silk cocoons were placed in 1000 mL of 0.02 M sodium carbonate (Na2CO3) solution and degummed at 100 °C for 1 h. Rinse with deionized water (DI water) three times to remove sericin, and then dry in an oven at 60 °C for 12 h. The degummed silk fibroin (SF) was dissolved in a ternary solvent system of CaCl2 / ethanol / H2O at 75 °C for 1 h. The obtained SF solution was dialyzed with a dialysis bag with a molecular weight cutoff of 3500, and the dialysate was DI water. The dialysis was performed for 3 days, during which the water was changed 3 times a day. Impurities and precipitated proteins were removed by high-speed centrifugation at 9000 rpm at 4 °C for 20 min, and the purified SF was then freeze-dried; (2) Preparation of SF-P-Gd hydrogel: 1 g SF was dissolved in a mixed solution of 7% (w / w) hexafluoroisopropanol (HFIP) and 98% (w / w) formic acid (volume ratio 9:1). 1 g PHMB and 0.4 g Gd(NO3)3·6H3O were added to the SF solution to prepare SF-P-Gd fiber hydrogel. The hydrogel was prepared using an electrospinning device (TongLi, China) under the following parameters: voltage 20 kV, distance between needle and collector 15 cm, flow rate 2 mL / h, rotation speed 800 rpm, and the collected fiber hydrogel was vacuum dried at 60 °C for 12 h, then cross-linked in anhydrous ethanol and rehydrated in phosphate buffered saline (PBS).

[0029] Test example (1) Structural characterization: The chemical structures of PHMB, VAN, PV, and PVG were analyzed using Fourier transform infrared (FT-IR) spectrometer (Nicolet 5700, USA) and ultraviolet-visible spectrometer (UV-Vis) (Bruker 400M, Germany).

[0030] (2) Morphological characterization of SF-PVG: The morphology of the fiber hydrogel was observed using a scanning electron microscope (SEM) (Thermo Scientific, USA) at a magnification of 5000 times in backscattering mode. The fiber diameter and angle distribution were quantitatively analyzed using ImageJ software, and at least 100 fibers were analyzed in each field of view.

[0031] (3) SF-PVG mechanical properties test: The mechanical properties of the fiber hydrogel were measured using a uniaxial tensile machine (CellScale, Canada). The samples were cut into strips (10 mm × 30 mm). The clamping distance was set to 20 mm and the tensile rate was 40 mm / min.

[0032] (4) Antibacterial adhesion ability test: Gram-negative bacteria Escherichia coli (E. coli, ATCC 25923) and Gram-positive bacteria Staphylococcus aureus (S. aureus ATCC 25923) were used as model microorganisms to evaluate the adhesion of bacteria on fiber hydrogels. A 10 mm diameter disc-shaped hydrogel was placed in a 48-well plate. Each disc hydrogel was incubated in 300 μL of bacterial suspension (1×10 8 CFU / mL) in PBS for 4 h. Subsequently, the bacteria attached to the fiber hydrogel were observed using SEM and quantified by the spread plate method. The bacterial survival rate was calculated as follows: (M1 / M2) × 100%; where M1 is the number of bacteria after fiber hydrogel treatment and M2 is the number of bacteria before fiber hydrogel treatment.

[0033] (5) Biofilm formation: Each disc-shaped hydrogel with a diameter of 10 mm was placed in each well of a 48-well plate and then incubated in 300 μL of bacterial suspension with a bacterial concentration of 1×10 6 CFU / mL (E. coli in nutrient broth (NB), S. aureus in tryptone soy broth (TSB)) for 24 h. The biofilm formed on the fiber hydrogel was observed using SEM, and the number of viable bacteria was quantified by the spread plate method.

[0034] (6) Hemolytic test: Rabbit blood was centrifuged at 1500 rpm for 10 min to separate red blood cells (RBC). Each hydrogel sample (area 1.7 cm 2 ) were immersed in 1 mL of 5% (v / v) RBC suspension, incubated at 37°C for 2 h, and then centrifuged at 1500 rpm for 10 min. The optical density (OD) of the supernatant at 575 nm was measured to calculate the hemolysis rate. PBS and DI water were used as negative and positive controls, respectively. The hemolysis rate was calculated as follows: (OD 样品 -OD 负对照 ) / (OD 正对照 -OD 负对照 )×100%.

[0035] (7) Cytotoxicity assay: The hydrogel was immersed in Dulbecco's modified Eagle's medium (DMEM) at a ratio of 6 cm² / mL and incubated at 37°C for 24 h to prepare the extract. 1 mL of L929 fibroblasts (ATCC) and HUVECs (ATCC) were seeded into 48-well plates at a cell density of 1×10 4 cells / mL. After 24 h, the medium was replaced with hydrogel extract and cultured for another 24 h. Cell viability was assessed using the CCK-8 kit (APExBIO, USA) and the live / dead staining kit (Biyuntian Biotechnology, China) according to the manufacturer's instructions.

[0036] (8) Cell proliferation assay: Each disc-shaped hydrogel with a diameter of 10 mm was placed in each well of a 48-well plate and then incubated in 500 μL of HUVECs-containing culture medium. On days 1, 3, and 5, the activity of HUVECs was assessed using a CCK-8 kit and a live / dead staining kit. After staining, the cell morphology was observed using SEM and ultra-high-resolution laser scanning confocal microscopy (Carl Zeiss, Germany), and the cell nucleus and cytoskeleton were stained with 4',6-diamidino-2-phenylindole (DAPI) and phalloidin, respectively.

[0037] (9) In vivo wound healing experiment: Full-thickness wounds with a diameter of 10 mm were created on the back of Sprague Dawley rats. To induce infection, each wound was inoculated with 100 μL of Staphylococcus aureus suspension (1×10 8 CFU / mL, PBS). The control group did not receive any treatment, while the other groups were treated with medical gauze, SF-PVG, and SF-PVGA hydrogels, respectively. Medical gauze, SF-PVG, and SF-PVGA hydrogels were changed three times a day, and adhesive bandages were used to fix the dressings to prevent them from falling off. On the 7th day, the rats were killed, and the collected tissues were homogenized in 500 μL PBS, and the homogenates were cultured on agar plates for quantitative analysis.

[0038] (10) Data processing: Each experiment was repeated at least three times, and all data are expressed as mean ± standard deviation. Statistical significance was determined using one-way analysis of variance (ANOVA) and Student's t-test. p < 0.05 was considered statistically significant (* for p < 0.05, ** for p < 0.01, *** for p < 0.001, **** for p < 0.0001).

[0039] Test results (1) Structural characterization ① Characterization of PVG: PVG was synthesized by a two-step method under mild conditions (see Figure 1 A). In the first step, the Schiff base PV was prepared by the imine condensation reaction of PHMB and VAN. This reaction was confirmed by the red shift of the benzene ring peak. In the UV-visible absorption spectrum, the benzene ring peak of VAN was red-shifted from 330nm to 400nm of PV (see Figure 1 B). In the second step, the lone pairs of electrons on the N and O atoms in PV interact with Gd 3+ The empty orbitals of the benzene ring interact with each other to form PVG. This interaction causes the absorption peak of the benzene ring to blue shift from 400nm of PV to 385nm of PVG (see Figure 1B), which can be attributed to the reduction of π electron density in PVG. Further characterization was performed by Fourier transform infrared spectroscopy (FT-IR) (see Figure 1 C). Compared with PHMB, PV at 1252 cm -1 A new absorption peak is shown at 1600 cm-1, which corresponds to the CO stretching vibration of the phenolic hydroxyl group in VAN. -1 A new absorption peak appeared at , indicating that the N atoms in PV successfully bonded with Gd 3+ In addition, the absorption peak (1252 cm -1 ) disappears and is replaced by a new absorption peak at 954 cm -1 This may be due to the O atom of the hydroxyl group in PV interacting with Gd 3+ Due to coordination.

[0040] ② Characterization of SF fiber hydrogel: SF fiber hydrogel was prepared by electrospinning, and its FT-IR spectrum ( Figure 2 A) at 1642, 1514 and 1232 cm -1 The SF hydrogels were cross-linked in anhydrous ethanol, resulting in a structural transformation from a random coil to a β-folded structure. This transformation was confirmed by the red shift of the characteristic bands of amide I and amide III, which moved to 1620 cm-1, respectively. -1 and 1227cm -1 The cross-linked SF hydrogels retained their original shape when immersed in phosphate-buffered saline (PBS) ( Figure 2 B). Figure 2 As shown in C, the cross-linked SF fiber hydrogel has a good three-dimensional structure. Figure 2 As shown in D-2E, after PHMB was incorporated into SF hydrogel (denoted as SF-P hydrogel), the fiber diameter increased from 524±165.8nm to 1197±219.3nm, accompanied by an increase in surface pores. This phenomenon may be attributed to the electrostatic interaction between the carboxyl group of the glutamyl side chain in SF and the guanidine group in PHMB. In addition, the terminal amino group of PHMB promotes the formation of intermolecular hydrogen bonds, thereby increasing the viscosity of the spinning solution and causing the fibers to become thicker. When PV was introduced into SF hydrogel to form SF-PV hydrogel, the polarity of the spinning solution decreased, resulting in a decrease in the fiber diameter to 1077±337.0nm. SF-PVG hydrogel was obtained by incorporating PVG into SF hydrogel, and Gd 3+The presence of enhanced the conductivity of the spinning solution and helped to form more stable and thinner fibers with a diameter of 684.3 ± 281.3 nm. The mechanical properties of these fiber hydrogels were evaluated by uniaxial tensile tests. Figure 2 As shown in F-2G, the Young's modulus of the hydrogel ranged from 2 MPa to 8 MPa, which is comparable to that of human skin, indicating good tensile strength. Among the different hydrogels, the SF-PVG fiber hydrogel exhibited the highest elongation at break, which was attributed to the electrostatic interaction between PVG and SF, which made the stress distribution more effective during stretching. In contrast, although the SF-P fiber hydrogel exhibited the highest Young's modulus, its cross-sectional fiber density was lower, making it more susceptible to breakage under tension.

[0041] (2) Effect of SF-PVG on bacterial adhesion: Bacterial adhesion to biomaterials may lead to infection, inflammation and subsequent immune response. To study the effect of PVG incorporated into SF fiber hydrogels on bacterial adhesion, the hydrogels were incubated in PBS at 10 8 CFU / mL concentration of bacterial suspension was incubated for 4 hours. Figure 3 As shown in Table 1-2. Figure 3 As shown in Table 1-2, after 4 h of incubation, the number of live Escherichia coli and Staphylococcus aureus attached to SF and SF-Gd hydrogels was similar, indicating that Gd alone 3+ The antibacterial effect is not good; the number of live bacteria and cell survival rate of Staphylococcus aureus attached to SF-P and SF-P-Gd decreased by 2-3 times compared with SF-Gd. This significant reduction is mainly attributed to the bactericidal activity of PHMB, which achieves antibacterial effect by destroying bacterial cell membranes and inhibiting key life processes of cells. Compared with SF, SF-Gd, SF-P-Gd and SF-PV, the number of live bacteria and cell survival rate of Staphylococcus aureus attached to SF-PVG were both 0. It can be seen that the antibacterial effect of SF-PVG is better than that of SF, SF-Gd, SF-P-Gd and SF-PV.

[0042] Table 1 Adhesion of different fiber hydrogels to bacteria - bacterial count

[0043] Table 2 Adhesion of different fiber hydrogels to bacteria-bacterial survival rate (%)

[0044] (3) Effect of SF-PVG on biofilm formation: When bacteria combine with nutrient-rich wound exudate in wounds, they may develop extensive proliferation and biofilm formation. If not effectively controlled, this process will significantly increase the risk of wound infection. Biofilms are structured groups of bacteria that are encapsulated by a self-secreted extracellular matrix (ECM) and exhibit enhanced resistance to antibiotic treatment and host immune responses. Therefore, inhibiting biofilm formation is critical for preventing infection and promoting wound healing. In order to evaluate the performance of different fiber hydrogels in inhibiting biofilm formation, these hydrogels were co-cultured with suspensions of Staphylococcus aureus and Escherichia coli in tryptone soy broth and nutrient broth for 24 hours, respectively. A large bacterial load was observed on the surface of SF and SF-Gd hydrogels, especially the biofilm formation of Staphylococcus aureus was obvious (see Figure 4 A). In contrast, the number of bacteria on SF-P and SF-PV hydrogels was significantly lower. Notably, the fiber surfaces of SF-P and SF-PV hydrogels appeared rough, which may be because PHMB disrupted the structural integrity of the bacteria, causing the cytoplasm to leak out and attach to the hydrogel surface. This attachment hinders the antibacterial effect because it promotes bacterial colonization. In contrast, there were almost no bacteria on the surface of SF-PVG hydrogel, and its fiber surface roughness was lower than that of SF-P and SF-PV hydrogels, indicating reduced attachment of bacterial cytoplasm. The antibacterial mechanism of PHMB includes its positively charged biguanide groups interacting with negatively charged phospholipids on the bacterial cell membrane through electrostatic interaction, which disrupts the integrity of the membrane and ultimately leads to bacterial cell death. In addition, Gd 3+ Can interfere with Ca on the surface of bacteria 2+ Binding sites, disrupting membrane integrity and biofilm formation. PHMB and Gd 3 + The synergistic antibacterial effect of SF-PVG hydrogel can be understood as the interaction of these two different mechanisms, rather than targeting specific proteins or membrane structures that exist only in Gram-positive or Gram-negative bacteria. Our experimental results further verified this view, showing that SF-PVG hydrogel has significant antibacterial activity against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli.

[0045] As shown in Table 3-4, after 24 h of co-culture, the number of viable bacteria on SF-Gd hydrogel was comparable to that on SF hydrogel; compared with SF-Gd, the number of viable bacteria and bacterial survival rate of Staphylococcus aureus on SF-PVG hydrogel were both reduced by 1.5×10 5times, while the number of live bacteria and bacterial survival rate of Escherichia coli were reduced by 400 and 2000 times, respectively; compared with SF-P, the number of live bacteria and bacterial survival rate of Staphylococcus aureus in SF-PVG hydrogel were reduced by 100 times, while the number of live bacteria and bacterial survival rate of Escherichia coli were reduced by 100 and 500 times, respectively; compared with SF-P-Gd, the number of live bacteria and bacterial survival rate of Staphylococcus aureus in SF-PVG hydrogel were reduced by 120 and 200 times, respectively, while the number of live bacteria and bacterial survival rate of Escherichia coli were reduced by 100 and 400 times, respectively; compared with SF-PV, the number of live bacteria and bacterial survival rate of Staphylococcus aureus in SF-PVG hydrogel were reduced by 10 and 20 times, respectively, while the number of live bacteria and bacterial survival rate of Escherichia coli were reduced by 4 and 20 times, respectively. It can be seen that the antibacterial effect of SF-PVG is better than that of SF, SF-Gd, SF-P-Gd and SF-PV. In addition, SF-PVG significantly improved the inhibitory effect of biofilm formation, highlighting their superior ability in preventing biofilm formation. These results suggest that SF-PVG antimicrobial fiber hydrogels can be used as candidate materials for the treatment of wound infections.

[0046] Table 3 Effects of different hydrogels on bacterial biofilm formation - bacterial number

[0047] Table 4 Effects of different hydrogels on bacterial biofilm formation - bacterial survival rate (%)

[0048] (4) Biocompatibility of SF-PVG: The biocompatibility of SF-PVG is crucial for its safe and effective application in wound healing. The blood compatibility of these hydrogels was evaluated by using deionized water and PBS as positive and negative controls. Figure 5 As shown in Figure 2, the hemolysis rate of all fiber hydrogels was less than 1%, indicating that they have excellent blood compatibility. In addition, we evaluated the cytotoxicity of the hydrogels using the extraction method and conducted experiments using L929 fibroblasts. Figure 6 As shown in A, after culturing in the hydrogel extract for 24 h, live / dead cell staining showed that most cells were stained green (indicating live cells), while only a few cells were stained red (indicating dead cells). Cell viability was quantified by the CCK-8 method, and the cell viability of all fibroblasts treated with different fiber hydrogels was over 90% (see Figure 6 B), further confirming the excellent cytocompatibility of these hydrogels with fibroblasts.

[0049] (5) Effect of SF-PVG on cell proliferation: ① In addition to fibroblasts, endothelial cells also play an important role in wound healing, mainly by promoting angiogenesis. Therefore, the proliferation of human umbilical vein endothelial cells (HUVECs) cultured on different fiber hydrogels was studied on days 1, 3, and 5. Figure 7 As shown in the figure, HUVECs grew well on SF-PVG and SF-PVGA hydrogels, and the proliferation rate was comparable to that on SF hydrogels. However, the proliferation of HUVECs on SF-PV hydrogels was significantly lower than that on SF and SF-PVG hydrogels, indicating that cytotoxicity may exist. This cytotoxicity may come from the Schiff base group of PV, which can chelate intracellular metal ions and disrupt their balance, thus being detrimental to cell proliferation.

[0050] ② In order to study the effect of fiber arrangement on cell growth, scanning electron microscopy (SEM) was used to observe the attachment and expansion of cells on different fiber hydrogels. Figure 8 As shown, HUVECs on SF-PVGA hydrogels were aligned along the fiber alignment direction, showing larger extension area and stronger cell-cell connections than cells on randomly oriented fiber hydrogels. Fig. 9 ) Observation of cell morphology revealed that HUVECs on SF and SF-PVG hydrogels were mainly spherical with limited extension, while cells on SF-PV hydrogels exhibited a disrupted cytoskeleton. In particular, cells on SF-PVGA hydrogels were aligned along the direction of hydrogel fiber alignment. Oriented surface morphology affects cell growth through two key mechanisms: first, the aligned fibers provide uneven stress distribution in the lateral and transverse directions, limiting the lateral extension of cells; second, finely aligned fibers provide a larger specific surface area, providing more attachment points, thereby enhancing cell extension.

[0051] (5) In vivo wound healing effect of SF-PVG: In order to evaluate the therapeutic effect of fiber hydrogel in infected wounds, a rat model of wounds infected with Staphylococcus aureus was established. In the first 3 days, the wounds of the control group and gauze treatment showed obvious infection, with yellow pus on the wound surface ( Fig.10 A). Wound area assessment ( Fig.10 B) shows that the wound surface treated with SF-PVG and SF-PVGA hydrogels reduced the wound surface area by 52% and 56% respectively on day 7 compared with the control group. Fig.10 C and 10D show that the bacterial load in wounds treated with SF-PVG and SF-PVGA hydrogels was reduced by 78% and 93%, respectively, compared with the control group at day 7. The significant improvement in wound healing highlights the antibacterial efficacy of the fiber hydrogel and demonstrates its potential in promoting tissue regeneration.

[0052] In summary, the present invention has developed a highly efficient antibacterial fiber hydrogel SF-PVG, which can inhibit the growth of Escherichia coli and Staphylococcus aureus at a low concentration (4μg / mL). The SF-PVG fiber hydrogel with oriented structure and excellent antibacterial properties was prepared by electrospinning technology. In addition, the oriented arrangement of the fibers combined with the interaction between SF and PVG enhanced the mechanical properties of the hydrogel. The SF-PVG fiber hydrogel also showed good biocompatibility, and its hydrogel fibers simulating the oriented arrangement of the extracellular matrix (ECM) promoted the adhesion, expansion and growth of mammalian cells. The present invention proposes a simple and promising strategy for the preparation of dressings for the treatment of wound infections.

[0053] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An antibacterial fiber hydrogel with high mechanical strength, characterized in that: The invention comprises a fiber hydrogel loaded with polyhexamethylene biguanide, o-vanillin and gadolinium ions; wherein the fiber hydrogel also comprises silk fibroin.

2. The method for preparing the antibacterial fiber hydrogel with high mechanical strength according to claim 1, characterized in that: The following steps are involved: (1) After removing the gelatin from the silkworm cocoons and washing them, the products are dried and dissolved in a solvent, reacted at 75-85°C for 1-2 hours, dialyzed and centrifuged, purified and freeze-dried to obtain silk fibroin; (2) dissolving polyhexamethylene biguanide and o-vanillin in a solvent respectively, then dropping o-vanillin into the polyhexamethylene biguanide solution, reacting for 2.5-3.5 hours, and removing the solvent to obtain a PV composite; (3) Dissolving the PV complex in a solvent, then adding a solution containing gadolinium ions to react for 2-3 hours, and then removing the solvent to obtain the PVG complex; (4) The silk fibroin prepared in step (1) is dissolved in a solvent, and then the PVG complex prepared in step (3) is added to prepare a fiber hydrogel. The product is vacuum dried, cross-linked, and then hydrated to obtain a hydrogel.

3. The preparation method according to claim 2, characterized in that: The solvent in step (1) is a mixed solution of CaCl2 / ethanol / H2O, and the molar ratio of CaCl2 / ethanol / H2O is 1:1-5:5-10.

4. The preparation method according to claim 2, characterized in that: In step (2), the concentration of polyhexamethylene biguanide is 0.025-0.125 g / mL; the concentration of o-vanillin is 1.25-2.5 mg / mL; and the solvent is methanol.

5. The preparation method according to claim 2, characterized in that: The solution containing gadolinium ions in step (3) is at least one of gadolinium chloride, gadolinium nitrate, gadolinium oxalate, gadolinium acetate and gadolinium sulfate; the concentration of the PV complex is 0.0625-0.025 g / mL; and the solvent is methanol.

6. The preparation method according to claim 2, characterized in that: In step (4), the mass ratio of the silk fibroin to the PVG complex is 20-40:1; and the solvent is hexafluoroisopropanol and formic acid.

7. The preparation method according to claim 5, characterized in that: The preparation parameters of the fiber hydrogel in step (4) are: voltage 15-25 kV, distance between the needle and the collector 10-20 cm, flow rate 2-3 mL / h, and rotation speed 800-2400 rpm.

8. Use of the antibacterial fiber hydrogel with high mechanical strength as claimed in claim 1 in the preparation of wound infection drugs.

9. The use according to claim 8, characterized in that: The traumatic infection includes burn wounds, diabetic foot ulcers, pressure injuries and lower extremity venous ulcers.

10. The use according to claim 8, characterized in that: The medicine is a wound dressing.